2019
DOI: 10.1017/hpl.2019.24
|View full text |Cite
|
Sign up to set email alerts
|

Rapid growth and properties of large-aperture 98%-deuterated DKDP crystals

Abstract: In this paper, a highly deuterated potassium dihydrogen phosphate (DKDP) crystal with sizes up to 318 mm × 312 mm × 265 mm was grown by the rapid-growth method. The synthesis tank device was specially designed to synthesize a higher deuterium concentration and high-purity DKDP solution. The deuterium content of the as-grown crystal, which was 97.9%, was determined by two methods, including infrared (IR) spectroscopy and thermo-gravimetric analysis (TGA) measurements. The performances of the 97.9% DKDP crystal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Zhang et al successfully used point-seed rapid growth technology to grow DKDP crystals with a deuterium content of 98% 31 , 32 . In 2019, Cai et al reported that a highly deuterated DKDP crystal with sizes up to 318 mm × 312 mm × 265 mm was grown by the rapid-growth method 33 . This demonstrates that growth by the rapid growth method not only shortens the growth period but also avoids the disturbance of monoclinic crystals, especially for the growth of highly deuterated DKDP crystals.…”
Section: Crystal Growthmentioning
confidence: 99%
“…Zhang et al successfully used point-seed rapid growth technology to grow DKDP crystals with a deuterium content of 98% 31 , 32 . In 2019, Cai et al reported that a highly deuterated DKDP crystal with sizes up to 318 mm × 312 mm × 265 mm was grown by the rapid-growth method 33 . This demonstrates that growth by the rapid growth method not only shortens the growth period but also avoids the disturbance of monoclinic crystals, especially for the growth of highly deuterated DKDP crystals.…”
Section: Crystal Growthmentioning
confidence: 99%
“…Near 900 nm central wavelength, many nonlinear crystals, such as lithium triborate (LBO) and deuterated potassium dihydrogen phosphate (DKDP), can realize over 200 nm bandwidth when pumped with high-energy frequency-doubled Nd:YAG or Nd:glass lasers. Especially, the existing crystal growth technologies can support large DKDP crystals over 400 mm size [10]. Therefore, the DKDP-based OPCPA scheme is considered a promising approach for developing 100 PW-class laser facilities.…”
Section: Introductionmentioning
confidence: 99%
“…It has been considered in many research studies that the laser damage was induced by localized absorption by either foreign nanoparticles incorporated during growth or intrinsic defect clusters formed during crystal growth [13][14][15]. Even though substantial improvements are made in DKDP growth technology to reduce defects over the past several years [16][17][18][19], the actual LIDT is still much lower than the theoretical value. Therefore, clarifying the LID mechanism is urgently needed.…”
Section: Introductionmentioning
confidence: 99%